Leadership Dynamics on Daily Workers in the Hotel Sector: A Conceptual Review - Rahayuningtyas, Bulan Aulia; Hapsari, Izzul Atsani Aries; Asshofi, Izza Ulumuddin Ahmad (SABA: Journal of Tourism Research, 2025)
This article discusses the application of leadership in organizational culture in relation to everyday workers in the hotel industry in Central Java. World The hotel industry is an important service industry in most countries in the world, especially in terms of attracting tourists for holidays and business events. Leadership is important in organizations because leadership is one of the keys to achieving organizational success. All decisions, actions and development steps require leadership. The main reason why leadership is important is because it is the foundation for fostering creativity and building strong teams. It should be noted that leadership is closely related to organizational culture, good leadership in an organization will give birth to a good organizational culture and support organizational productivity. Organizational culture is a habit that is maintained over time and is used and applied in work activities as a driving force to improve the work quality of employees and managers of a company. The aim of this research is to identify leadership in implementing organizational culture in the hotel industry in Central Java. The method used in this research is descriptive qualitative through library research, namely research based on the study of books, journals and previous literature related to the research topic. Using library research methods, descriptive analysis will be used to interpret the data. The results of this research can be concluded that leadership plays an important role in the hotel industry and has a significant positive and negative influence on the performance of daily workers.